Weighted Lipschitz Estimate for Commutator of Bochner-Riesz Operators on Weighted Morrey Spaces (Analysis in Theory and Applications, 2014)
In this paper, we will use a method of sharp maximal function approach to show the boundedness of commutator $[b,T_{R}^{\delta}]$ by Bochner-Riesz operators and the function $b$ on weighted Morrey spaces $L^{p,\kappa}(\omega)$ under appropriate conditions on the weight $\omega$,  where $b$ belongs to Lipschitz space or weighted Lipschitz space.